2011
DOI: 10.1172/jci42975
|View full text |Cite
|
Sign up to set email alerts
|

The ability of LCRMP-1 to promote cancer invasion by enhancing filopodia formation is antagonized by CRMP-1

Abstract: Metastasis is a predominant cause of death in patients with cancer. It is a complex multistep process that needs to be better understood if we are to develop new approaches to managing tumor metastasis. Tumor cell invasion of the local stroma is suppressed by collapsin response mediator protein-1 (CRMP-1). Recently, we identified a long isoform of CRMP-1 (LCRMP-1), expression of which correlates with cancer cell invasiveness and poor clinical outcome in patients with non-small-cell lung cancer (NSCLC).Here, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
74
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(79 citation statements)
references
References 51 publications
4
74
1
Order By: Relevance
“…In a heated antigen retrieval process (24), the slides were placed in an EDTA buffer (pH 8.0) and heated for 2 min in a steamer. The slides were incubated overnight at 4˚C with monoclonal mouse anti-human anti-ERβ2 (Serotec) and polyclonal goat anti-human anti-IL-12 Rβ2 (Santa Cruz Biotechnology, Inc., Dallas, TX, USA) antibodies (25) in bovine serum albumin prior to incubating with the secondary antibodies rabbit anti-mouse immunoglobulin G (IgG) k-chain specific antibody (SAB3701212; 1:100, Sigma-Aldrich) or rabbit anti-goat IgG F(ab')2 (SAB3700244; 1:100; Sigma-Aldrich) at RT for 20 min. Color was developed in 3,3'-diaminobenzidine (DAB) solution for 10 min followed by counterstaining with Harris hematoxylin.…”
Section: Methodsmentioning
confidence: 99%
“…In a heated antigen retrieval process (24), the slides were placed in an EDTA buffer (pH 8.0) and heated for 2 min in a steamer. The slides were incubated overnight at 4˚C with monoclonal mouse anti-human anti-ERβ2 (Serotec) and polyclonal goat anti-human anti-IL-12 Rβ2 (Santa Cruz Biotechnology, Inc., Dallas, TX, USA) antibodies (25) in bovine serum albumin prior to incubating with the secondary antibodies rabbit anti-mouse immunoglobulin G (IgG) k-chain specific antibody (SAB3701212; 1:100, Sigma-Aldrich) or rabbit anti-goat IgG F(ab')2 (SAB3700244; 1:100; Sigma-Aldrich) at RT for 20 min. Color was developed in 3,3'-diaminobenzidine (DAB) solution for 10 min followed by counterstaining with Harris hematoxylin.…”
Section: Methodsmentioning
confidence: 99%
“…A previous study showed that LCRMP-1 overexpression promoted cancer cell invasion in vitro and in vivo, and that it was associated with poor overall and disease-free survival in NSCLC patients (8). It has also been shown that LCRMP-1 enhances filopodia formation and is phosphoregulated by glycogen synthase kinase 3β in NSCLC cells (9,13). The results of these previous studies led the present study to investigate the role of LCRMP1 in OS progression.…”
Section: Discussionmentioning
confidence: 77%
“…Therefore, novel approaches for diagnosis and novel drug targets are required. It has been reported that LCRMP-1 promotes the migration and invasion of NSCLC cells (8,9). In addition, increased expression of N-cadherin and MMPs following LCRMP-1 upregulation has confirmed that LCRMP-1 has a significant role in the migration, invasion and metastasis of tumor cells, as N-cadherin and MMPs are involved in epithelial-mesenchymal transition and remodelling of the extracellular matrix (19,20).…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…24 In fact, CRMP1 can suppress cancer cell invasion through F-actin depolymerization, while its isoform, LCRMP1, can promote cancer cell migration through actin polymerization and filopodia formation. 25 This is an interesting example of a negative feedback mechanism by protein isoforms in a living cell.…”
Section: Crmps and Non-immune Cell Migrationmentioning
confidence: 99%